613 QTC PROLUNGATION IN TAKOTSUBO: DIFFERENT PATTERN, DIFFERENT OUTCOME?. (15th December 2022) - Piccolo, Solange; Dotto, Alberto; Rizzetto, Francesca; Lia, Micaela; Widmann, Maddalena; Pazzi, Sara; Ferrigni, Francesca; Tomasi, Luca; Scarsini, Roberto; Prati, Daniele; Castaldi, Gianluca; Ferrero, Valeria; et al.
Abstract: Introduction: QT prolongation has been widely described in Takotsubo Syndrome (TTS), but the pathophysiology and prognostic implications remain unclear, and it can still hold some surprise. We have noticed two different populations based on electrocardiogram (ECG) findings that weren't described before. The aim of the study was to investigate the difference between the two of them, with a focus on prognosis. Methods: FEATURES (A) V5 (B)V2 Number 42 25 Female 36(85%) 24 (96%) Average age 72, 7±12 72, 8±9, 8 Hypertension 29 (69%) 17(68%) Diabetes 5 (12%) 4(16%) dyslipidemia 16 (38%) 12(48%) COPD 6 (14%) 2(8%) CKD 2 (4%) 1(4%) Hospital stay (days) 9, 3±5, 7 8 ±2, 8 SupraV. arrythmyas 6 6 V. arrythmyas 2 3 EF at presentation 38, 1±10 37±5 Death 10 1 QTc (msec) 531±59 525, 6 ±57 ECG axis 19, 7±50 26±42 Median FU (years) 3, 51 3, 07 We retrospectively analyzed in-hospital ECG from TTS (based on revised Mayo Clinic criteria) from 2014 to August 2022. QT interval was manually measured and corrected with Bazzett formula. Patients with bundle branch blocks or QT shorter than 460 (male), 470 msec (female) were excluded. The population was divided into two groups, based on the lead with the longest QT: V5 (group A) or V2 (group B). Our primary endpoint was overall mortality. Secondary outcome ware either ventricular or supraventricular arrhythmias detected before discharge. Results: Our final cohort was composed of 67 patients, 42 of which had the maximum QTc interval in V5 (group A) and the other 25 having the longest QTc in V2 (group B). These two populations did not differ much in terms of age, sex, comorbidities, and echocardiographic findings at presentation. Despite this, we observed a significant prognostic difference: patients in group B experienced more in-hospital arrhythmias than the other subgroup (p=0.035), but after a median follow up of 3.6 years their all-cause mortality was significantly lower (p=0.034). Conclusion: Although quite similar in demographic characteristics and presentations, we observed that patients with longer QTc in V5 lead (Group A) seem to have a higher mortality rate, in comparison with patients with longer QTc in V2 (Group B). It could help to identify a high-risk subgroup of patients. This is a preliminary study, further investigation is needed to make more reliable inferences.